Visualizing the Nexus of Job Crafting and Work-Family Enrichment: A Bibliometric Mapping Approach - Ariani, Gusti Meinar Girda; Hasanah, Nurul; Yulianty, Farida; Syahrani; Wicaksono, Teguh (CV ODIS, 2025)
This study aims to systematically map and visualize the intellectual structure and thematic development of scholarly work on the relationship between job crafting and work-family enrichment. Despite the growing academic interest in both constructs, existing literature remains fragmented, with limited integration across domains. Using a bibliometric mapping approach, this study analyzes 300 peer-reviewed articles published between 2020 and 2025, retrieved from Scopus and Google Scholar. Data collection followed the PRISMA protocol to ensure transparency and methodological rigor. The bibliographic data were processed using VOSviewer to generate network, overlay, density, and co-authorship collaboration visualizations. The results reveal that job crafting remains the conceptual core of the literature, frequently linked with job satisfaction, autonomy, and work engagement, while work-family enrichment has only recently gained prominence, especially in response to global shifts such as remote work and increased work-life demands. Overlay analysis highlights emerging keywords such as resilience, recognition, and remote work, while density visualization reveals underdeveloped themes that represent future research opportunities. Co-author collaboration networks show limited interdisciplinary and international collaboration, emphasizing the need for more inclusive research ecosystems. The study contributes theoretically by reinforcing the relevance of integrating the Job Demands-Resources model, Self-Determination Theory, and Role Enrichment Theory. Practically, the findings inform organizations about the importance of proactive job design in fostering positive work-family dynamics. Methodologically, this research demonstrates the utility of bibliometric mapping in identifying gaps, knowledge clusters, and research fronts in an evolving interdisciplinary field